Resiliency of Singkil Coastal Vegetation due to Natural Catastrophes - Onrizal Onrizal; Mashhor Mansor; Nurdin Sulistiyono (Hasanuddin University, 2015)
Aceh Singkil west coast of Northern Sumatra was affected by natural catastrophes both tsunami and coastal deformation. Apparently most of the inter-tidal vegetation communities suffered because of the inundation intensity and duration changed. Investigation was carried on the structure and composition of littoral and mangrove forests in Singkil coast for 52 and 49 months after the 2004 and 2005 natural catastrophes, respectively. In each vegetation type, data were collected from four sampling plots, each measuring 30 m x 30 m. The sampling plots were separated into 10 m x 10 m sub-plots for matured trees and 5 m x 5 m sub-plots for smaller trees or shrubs. All plants within the subplots were identified and counted. Pure stand of littoral forests were dominated by Casuariana equisetifolia in the mature stage and Cerbera manghas in regeneration stages as natural regeneration. In the mangrove area, most of the mangrove trees such as Bruguiera gymnorrhiza, B. parviflora, and Rhizophora apiculata dead. Sonneratia caseolaris was higher survival rate compared than mangrove trees. B. gymnorrhiza seedlings were growing well. Mangrove palm Nypa fruticans populations were recorded growing well and with a good resiliency and persistence. In fact some of coastal vegetations both in coastal dry lands and in wetland forests have a good capacity to naturally restore and grow after the environmental destruction. From ecological point of view, these plant species should be selected for rehabilitation program in the natural catastrophes both tsunami and coastal subsidence as the impact of large earthquake could be reduced.